Feminist imagery and its artistic interpretation in Neal Asher’s “Brass Man” and “The Line of Polity” - Umarkulova, Munira Zakhidjan kizi (The Lingua Spectrum, 2026)
This article examines the artistic interpretation of female characters in Neal Asher’s science fiction novels from a literary-critical perspective. The research draws on feminist and posthumanist theoretical approaches developed by Simone de Beauvoir, Judith Butler, Donna Haraway, N. Katherine Hayles, Rosi Braidotti, Teresa de Lauretis, Lucy Suchman, T.V. Kruvko, and D.D. Kadirova. The study argues that Asher’s protagonists Eldene and Mika embody a synthesis of gender critique and posthuman transformation. Eldene’s transition from oppression to agency reflects a process of feminist emancipation shaped by social and technological forces. In contrast, Mika’s cyborg transformation illustrates both the empowering and ambivalent dimensions of technological evolution. Through close literary analysis of key narrative episodes, the article demonstrates that Asher’s space opera engages deeply with issues of embodiment, identity, and subjectivity, showing how science fiction functions as a platform for exploring changing models of power, agency, and human transformation in technologically mediated futures.